Mapping Internal and External Barriers to Elementary Numeracy Policy Implementation: A PRISMA-Based Systematic Review - Alfaris, Renaldy; Sa’dijah, Cholis; Nusantara, Toto; Arifin, Slamet (Papanda Publisher, 2024)
This study systematically reviews 27 journals addressing autogenic obstacles in numeracy learning among elementary school students. Autogenic obstacles can be analyzed philosophically in terms of internal and external factors, which will inform more effective policy-making. Internal autogenic obstacles encompass math anxiety, cognitive limitations, and language comprehension, all of which significantly impact students' numeracy skills. Additionally, cognitive abilities such as number understanding, arithmetic operations, and symbolic representation are crucial to numeracy learning. External autogenic obstacles include unsupportive learning environments and limited resources, as well as theoretical teaching methods lacking contextualization and insufficient teacher competence in adopting student-centered approaches, which further impede numeracy development. This study also examines policies aimed at overcoming autogenic obstacles through teacher professional development, multisectoral collaboration, enhanced learning resources, and the implementation of periodic evaluations and constructive feedback, all of which are essential for ensuring the consistency and sustainability of numeracy improvement programs in elementary schools. This will enable readers to identify the challenges and their corresponding solutions.